Media and Participation: A site of ideological-democratic struggle - Carpentier, Nico (Intellect, 2011)
Participation has become fashionable again, but at the same time it has always played a crucial role in our contemporary societies, and it has been omnipresent in a surprisingly large number of societal fields. In the case of the media sphere, the present-day media conjuncture is now considered to be the most participatory ever, but media participation has had a long and intense history. To deal with these paradoxes, this book looks at participation as a structurally unstable concept and as the object of a political-ideological struggle that makes it oscillate between minimalist and maximalist versions. This struggle is analysed in theoretical reflections in five fields (democracy, arts, development, spatial planning and media) and in eight different cases of media practice. These case studies also show participation's close connection to power, identity, organization, technology and quality.